A vitrine da ciência pela perspectiva da agência Bori: uma análise de estratégias de divulgação tecnocientíficas por meio do jornalismo - Friedrich, Claudine Freiberger (2024)
In this dissertation, we analyze relationships established between journalism and science in a context marked by challenges to scientific dissemination that, despite having ancient roots, were brought to the fore by the Covid-19 pandemic and the scenario of cognitive disorientation that has arisen around of contemporary scientific dynamics (COSTA, 2020; ECHEVERRÍA, 2003; INNERARITY, 2022; NOWOTNY, 2005; OLIVEIRA, 2020, 2022). As an object of study, we have the Bori Agency - an unprecedented initiative in Brazil, which “arose with the mission of promoting a change in the country's scientific culture” (RIGHETTI et al., 2022, p.4) and has been operating, since 2020, disseminating scientific studies about to be published to guide the national press through journalists registered on an online platform. Taking into account that Bori defines itself as a kind of showcase of national science (RIGHETTI et al., 2022), we question: how is visibility attributed to science from the perspective of scientific dissemination of the Bori Agency? To answer this research problem, our general objective is to understand the strategies adopted by Agência Bori to meet its proposal of qualifying the connection between science and society through journalism. As specific objectives, we define: 1) identify which type of science is relevant to Bori; 2) identify which scientist profile is relevant to Bori; 3) investigate Bori's relationship with its partners and supporters; 4) analyze how Bori presents the scientific debate to society. Methodologically, we carried out an investigation of texts produced by Bori in 2022, with the application of an analytical protocol - based on Bardin's Content Analysis (CA) (2016) - inspired by the Ibero-American Protocol for Training and Monitoring in Scientific Journalism (RAMALHO et al., 2012); based on the results found, we collected data to form a profile of researchers used as journalistic sources by Bori; based on information available on the Bori website and a scientific article written by team members (RIGHETTI et al., 2022), we carried out an editorial analysis of the Institution; and we also conducted an interview with the Agency's content manager. As a result, we infer that the “scientific showcase” that Bori proposes to assemble has the purpose of strengthening Brazilian science, highlighting important discoveries for the local ecosystem. In the approach given by the Agency to scientific dissemination, however, where press relations criteria are mixed with journalistic values, uncertainties, controversies, risks, financing and other mediations intrinsic to scientific development are obscured, which makes it impossible for a critical conception of science to be brought to public debate. By meeting the demands of institutions that financially support its work, Bori grants visibility to science from a techno-scientific perspective, while economic values mix and, at times, stand out compared to epistemic ones, causing it to be instrumentalized, by Bori Agency, a type of communication at the service of technoscience marketing.